THE IMPACT OF THE PRO AND CONS POLICIES IN JOKOWI ERA'S ON THE MACRO ECONOMY OF SOCIETY - Akhmad Kusuma Wardhana (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2021)
Introduction: Corona is a new variant of the virus that spreads very quickly. It is only by physical contact the virus capable on infecting human body as its host. Governments in various countries have implemented social restrictions or lockdowns to reduce the spread of the virus.Methods This study uses descriptive analysis method. The sample of this study is Jokowi's three policies on handling corona.Results: Not all of the policies contrary considered for the public are detrimental. The lack of a lockdown from the start was due to save foreign exchange from the tourism sector before the lockdown occurred.Conclusion and suggestion: The social restriction policy has not only resulted in positive way for the medical community, but also negative way with the decline of the national economy.